Kajian rencana pembuatan kerangka mesin pemecah kemiri desa siboruan kecamatan Balige kabupaten Toba provinsi Sumatera Utara - Siahaan, Saloom Hilton; Purba, Jhon Sufriadi; Simanjuntak, Mario Geraldi; Situmorang, Regi Chandela (Papanda Journal of Mathematics and Science Research, 2025)
Candles (Aleurites moluccana) have numerous benefits for human life. This is evident in Siboruon Village, Balige District, Toba Regency, North Sumatra Province. Candlenuts are a major agricultural commodity and are quite abundant during the harvest season. Post-harvest candlenut processing is still relatively conventional, often done manually by directly pounding the candlenuts, resulting in less than optimal production capacity. Therefore, researchers will conduct a design that will facilitate the cracking of candlenut shells. The authors used experimental research, constructing tools and conducting direct testing on objects in Siboruon Village, Balige District, Toba Regency, North Sumatra Province, from January to December 2024. The main frame of the candlenut shell cracking machine was designed using ST 37 angled steel with an "L" profile measuring 40 x 40 x 4 mm. The tools used included welding, a cutting grinder, a rolling ruler, a steel ruler, a pin, a square, and a scraper. The steps involved in constructing the main frame of a candlenut shell-cracking machine are: 1) Preparation of working drawings, 2) Material cutting planning, 3) Cutting process, 4) Assembly process, 5) Welding process. Based on the results of this final project, a candlenut shell-cracking machine has been produced. After construction and functional testing, the frame is capable of supporting the load applied by other components and can support the machine properly